Postfeminism, hybrid mumpreneur identities and the reproduction of masculine entrepreneurship. (February 2022) - Lewis, Patricia; Rumens, Nick; Simpson, Ruth
Mobilising postfeminism as an analytical device, this article re-examines how women business owners discursively engage with the identity of the mumpreneur. Drawing on interviews with women business owners, this article reconceptualises the compatibility between motherhood and entrepreneurship associated with the mumpreneur, in terms of a hybrid identity that interlinks feminine and masculine behaviours connected to home and work. Study data reveal the discursive practices present in interview accounts – choosing family and work, strategic mumpreneurship and enhancing the business without limits – which draw on postfeminist discourses to constitute hybrid entrepreneurial femininities associated with the mumpreneur category. The article contributes to the gender and entrepreneurship literature, in particular, the scholarship on mumpreneurship, by first, showing how engagement with the mumpreneur identity is implicated in the reproduction of masculine entrepreneurship; second, demonstrates how encounters with the mumpreneur contribute to the creation of a hierarchy of entrepreneurial identities which reinforces the masculine norm; and third considers how the mumpreneur as a hybrid identity mobilises entrepreneurship in children in gendered ways. While the emergence of the mumpreneur as a contemporary entrepreneurial identity has positively impacted how women's entrepreneurship is viewed, the study demonstrates that it has not disrupted dominant discourses of masculine entrepreneurship or gendered power relations in the entrepreneurial field.